Second-Generation Antipsychotic Use in Pediatric Emergency Medicine. Issue 3 (March 2021) - Lambert, Clare; Panagiotopoulos, Constadina; Davidson, Jana; Goldman, Ran D.
Abstract: In recent years, the number of patients presenting to the emergency department with mental health complaints has been growing, alongside an increase in second-generation antipsychotic (SGAs) prescriptions for a variety of mental health conditions. Children treated with SGAs may have abnormalities, such as rapid weight gain and central adiposity, glucose intolerance, dyslipidemia, and hypertension; they may present to the pediatric emergency department with components of metabolic syndrome or type 2 diabetes, and a subsequent significant risk for cardiovascular complications later in life. Pediatric emergency department providers may serve as a safety net for patients to detect SGA-related metabolic complications, especially among vulnerable populations lacking access to primary care or psychiatric services.